The German labor market for older workers in comparative perspective - John S. Heywood; Uwe Jirjahn (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2015)
This paper focuses on the German labor market for older workers. It does so in comparison with other countries and with a unique focus on the role of employer incentives for retaining and hiring older workers. It argues that while employment of older German workers has improved due to changes in government policy, the labor market for older workers remains characterized by far less mobility and opportunity. While we recognize the potential explanations of reduced productivity and age discrimination, we review evidence pointing to the importance of life-cycle contracts (Hutchens 1986, Lazear 1979). These contracts can be efficient but typically imply that older workers will have difficulty being re-hired into career jobs after separation. We suggest that attempts to reduce or eliminate such life-cycle contracts are likely to be counter-productive but suggest how other countries, particularly Japan, have dealt with this issue.
Keywords: J14; J33; 330; older workers; deferred compensation; productivity; discrimination; labor market institutions